New data on efficacy of valacyclovir in secondary prevention of maternal–fetal transmission of cytomegalovirus. (3rd January 2023) - Egloff, C.; Sibiude, J.; Vauloup‐Fellous, C.; Benachi, A.; Bouthry, E.; Biquard, F.; Hawkins‐Villarreal, A.; Houhou‐Fidouh, N.; Mandelbrot, L.; Vivanti, A. J.; Picone, O.
ABSTRACT: Objective: Congenital cytomegalovirus (CMV) infection is the leading cause of non‐genetic hearing and neurological deficits. The aim of our study was to evaluate the efficacy and safety of valacyclovir (VCV) treatment in preventing CMV transmission to the fetus after maternal primary infection. Methods: This was a retrospective, multicenter study evaluating the rate of maternal–fetal CMV transmission in pregnancies with maternal primary CMV infection treated with VCV at a dosage of 8 g per day (VCV group) compared with a control group of untreated women. Each case underwent virological testing to confirm maternal primary infection and to provide accurate dating of onset of infection. The primary outcome was the presence of congenital CMV infection at birth diagnosed based on polymerase chain reaction analysis of saliva, urine and/or blood samples. The efficacy of VCV treatment was assessed using logistic regression analysis adjusted for a propensity score. Results: In total, 143 patients were included in the final analysis, of whom 59 were in the VCV group and 84 were in the untreated control group. On propensity‐score‐adjusted analysis, VCV treatment was significantly associated with an overall reduction in the rate of maternal–fetal CMV transmission (odds ratio, 0.40 (95% CI, 0.18–0.90); P  = 0.029). The rate of maternal–fetal CMV transmission, determined at birth, in the VCV vs control group was 7% (1/14) vs 10% (1/10) after periconceptional maternal primary infection ( P  = 1.00), 22% (8/36) vs 41% (19/46) after first‐trimester maternal primary infection ( P  = 0.068) and 25% (2/8) vs 52% (14/27) after second‐trimester maternal primary infection ( P  = 0.244). When analyzing the efficacy of VCV treatment according to maternal viremia at treatment initiation, there was a trend towards greater efficacy when patients were viremia‐positive (21% vs 43%; P  = 0.072) compared with when they were viremia‐negative (22% vs 17%; P  = 0.659). Maternal side effects associated with VCV were mild and non‐specific in most cases. Conclusion: Our findings indicate that VCV treatment of pregnant women with primary CMV infection reduces the risk of maternal–fetal transmission of CMV and may be effective in cases with primary infection in the first and second trimesters. © 2022 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Han and Li. Click here to view the Correspondence.